2018
DOI: 10.1080/13575279.2018.1481368
|View full text |Cite
|
Sign up to set email alerts
|

A randomised control trial of parent and child training programmes (versus wait list control) for children with ADHD-type behaviours: A pilot study

Abstract: Objective: A randomised control trial was conducted to assess whether the combined Incredible Years parent training and child training programmes (PT + CT) led to improvements in ADHD-type behaviours in children, when compared to a PT-only group and a Wait List Control (WLC) group. Method: Forty-five families with a child aged 3-7 years who displayed ADHD-type behaviours were referred for treatment and randomised to a combined treatment group (PT + CT; n = 12), a PT group (n = 19) or a WLC group (n = 14). Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The pooled sample size of participants across 24 studies was N= 2,329 (range 14-161) parents. Where parent gender was reported in studies, the majority were female mothers [45][46][47][48][49][50][51][52][53][54][55][56][57][58]. The remaining studies reported on measures provided by a 'parent' but did not specify the gender [59][60][61][62][63][64][65][66][67] .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pooled sample size of participants across 24 studies was N= 2,329 (range 14-161) parents. Where parent gender was reported in studies, the majority were female mothers [45][46][47][48][49][50][51][52][53][54][55][56][57][58]. The remaining studies reported on measures provided by a 'parent' but did not specify the gender [59][60][61][62][63][64][65][66][67] .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The average age of the child was 5.88 years (SD= 1.82; range 3.81 to 10.35 years). Selection of children into individual studies were based on them having either diagnosis of ADHD, CD or ODD [37,47,52,59, 67] , the children having externalising scores in the clinical range [37,46,48,[50][51][52][53]61, 63, 65, 66, 68, 69], or elevated symptoms of externalising behaviours that caused parental concern for their child and/or parenting [37, 45, 48, 50, 51, 56, 60-62, 64, 70-72]. Additionally, some studies included additional inclusion criteria: premature birth [68] giftedness [64], at risk for maltreatment [72], or placed in a licenced nonrelative foster home [53].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, literature had strongly suggested the effectiveness of the IYPP in improving children’s behaviors with small to large effect sizes ( Javier et al, 2016 ; Seabra-Santos et al, 2016 ; Morpeth et al, 2017 ; Murray et al, 2017 ; Weeland et al, 2017 ; Leckey et al, 2018 ; Leijten et al, 2018a ; Gardner et al, 2019 ; Karjalainen et al, 2019 ; van Aar et al, 2019 ). Except for Weeland et al (2017) , who studied the program’s effect on 4-8 year-olds, most of the recent IYPP studies focused on preschool children of a much younger age.…”
Section: Discussionmentioning
confidence: 99%
“…The final paper, "A randomised control trial of parent and child training programmes (versus wait list control) for children with ADHD-type behaviours: A pilot study" by Leckey et al (2018), describes a mixed methods study, conducted in the Republic of Ireland, which evaluates the combined Incredible Years parent training and child training programmes (PT + CT) in respect of outcomes for children with Attention Deficit Hyperactivity Disorder (ADHD). ADHD is described as a chronic and debilitating behavioural disorder that emerges in early childhood and is characterised by maladaptively high levels of inattention, hyperactivity and impulsivity (Harpin, 2005); it affects approximately 3-9% of children in the UK (National Institute for Health and Clinical Excellence, 2008).…”
Section: Editorialmentioning
confidence: 99%